Demonstration of the integrated rural energy planning framework for sustainable energy development in low-income countries: Case studies of rural communities in Nigeria. (July 2021) - Ugwoke, B.; Sulemanu, S.; Corgnati, S.P.; Leone, P.; Pearce, J.M.
Abstract: With the vast rural population, the availability of locational renewable energy resources and limited finances in low-income (developing) countries, there is the need for an integrated and holistic energy planning framework to unlock their potential for achieving energy-based economic development. The integrated rural energy planning framework provides a unified road map for energy planning and system design with renewable energy integration geared towards improving energy access in rural areas. Therefore, this study presents the application of case studies to this framework to foster improved localized renewable energy access in low-income (developing) countries. Using rural Nigeria as the geographic scope, the site identification and selection and the locational estimation of annual energy demand steps of the framework are performed for rural areas. Utilizing GIS-based tools, rural communities are identified, and their viable renewable energy resources are estimated. Adopting the reference building approach, seasonal disaggregated energy demand profiles are obtained at community scale with an hourly time-step. These are obtained in the absence of smart-metering equipment and measured datasets on energy use. The obtained results provide insights to inform localized energy policy design by combining rural electrification with energy conservation strategies. This framework has wide applicability across areas with similar energy access and rural development issues especially in sub-Saharan Africa and developing Asia. Highlights: Case study applications presented on the integrated the rural energy planning framework. "Brownfield" locations identification scheme to select low hanging fruits sites. Hourly energy demand profile obtained for rural areas without smart metering. Insights to inform localized energy policy design by combining rural electrification with energy conservation strategies.